Complex Autoantibody Responses Occur following Moderate to Severe Traumatic Brain Injury - Edward Needham; Oda Stoevesandt; Eric Peter Thelin; Henrik Zetterberg; Elisa R. Zanier; Faiez Al Nimer; Nicholas J. Ashton; Joanne Outtrim; Virginia Newcombe; Hani S. Mousa; Joel Simrén; Kaj Blennow; et al. (2021)
Most of the variation in outcome following severe traumatic brain injury (TBI) remains unexplained by currently recognized prognostic factors. Neuroinflammation may account for some of this difference. We hypothesized that TBI generated variable autoantibody responses between individuals that would contribute to outcome. We developed a custom protein microarray to detect autoantibodies to both CNS and systemic Ags in serum from the acute-phase (the first 7 d), late (6-12 mo), and long-term (6-13 y) intervals after TBI in human patients. We identified two distinct patterns of immune response to TBI. The first was a broad response to the majority of Ags tested, predominantly IgM mediated in the acute phase, then IgG dominant at late and long-term time points. The second was responses to specific Ags, most frequently myelin-associated glycopeptide (MAG), which persisted for several months post-TBI but then subsequently resolved. Exploratory analyses suggested that patients with a greater acute IgM response experienced worse outcomes than predicted from current known risk factors, suggesting a direct or indirect role in worsening outcome. Furthermore, late persistence of anti-MAG IgM autoantibodies correlated with raised serum neurofilament light concentrations at these time points, suggesting an association with ongoing neurodegeneration over the first year postinjury. Our results show that autoantibody production occurs in some individuals following TBI, can persist for many years, and is associated with worse patient outcome. The complexity of responses means that conventional approaches based on measuring responses to single antigenic targets may be misleading.